"Good Economics for Hard Times" - Adhikari, Naveen (Economic Journal of Nepal, 2021)
Abhijit V. Banerjee and Esther Duflo (2019), Good Economics for Hard Times, Published by Juggernaut Books, KS House, 118 Shahpurjat, New Delhi, 110049, India, Pages 403 (including index and Bibliography) + x, P-ISBN: 9789353450700 E-ISBN: 9789353450717